High-throughput fabrication of cell-laden 3D biomaterial gradients - Guimarães, C. F. (2020)
High-throughput strategies for optimizing biomaterials to direct cellular behaviour are a fundamental need for propelling tissue engineering and regenerative medicine. In 2D, biomaterialâ s gradients have proven to be powerful platforms for simultaneously screening several surface conditions. However, their translation to 3D is yet limited to 1) exploiting light-based crosslinking and 2) non-sequential, single-gradient production. We built a microfluidic platform that allows distinct hydrogel precursors, as fluids, to be gradually mixed and crosslinked into 3D gradient fibres. Herein, we report how this system can be used for the sequential fabrication of independent cell-laden libraries with gradients of polymer concentration, non-adhesive/adhesive materials and both ionic and light crosslinking mechanisms. Automated image analysis of hundreds of single-cell events as a function of position yielded trends and pinpointed best-fit conditions based on cell shape, adhesion, proliferation and triggering of stromal/stem cell differentiation. We deliver a simple, versatile, and complete approach towards fully high-throughput 3D gradient fabrication for cell/material screening and optimization.